Stalin's terror and the long-term political effects of mass repression. (March 2018) - Zhukov, Yuri M; Talibova, Roya
Repression has a long-term negative effect on political participation. Using millions of arrest records from archival documents, and polling station-level election results, we examine how exposure to Stalin-era repression affects voter turnout in Putin's Russia. To estimate the effect of repression on voting, we exploit exogenous variation in repression due to the structure of mid-century Soviet railroads, and travel distances to prison camps. We find that communities more heavily repressed under Stalin are less likely to vote today. The electoral legacy of Stalin's terror – decades after the Soviet collapse, and across multiple election cycles (2003–12) – is systematically lower turnout. To show that our result is not unique to the Putin regime, we replicate our analysis in Ukraine (2004–14), and find similar patterns. These results highlight the negative consequences of repression for political behavior, and challenge the emerging view that exposure to violence increases political engagement. While past research has emphasized the short-term effects of repression over several months or years, we show that these effects may be durable over generations and even changes of political regime. Our findings also demonstrate that repression need not be collective or indiscriminate to have community-level effects.